Study of Neighborhood Degree-Based Topological Indices via Direct and NM-Polynomial of Starphene Graph. (15th June 2022) - Afzal, Deeba; Hameed, Saira; Ashraf, Usman; Mehmood, Arif; Chaudhry, Faryal; Thapa, Dhan Kumari
Abstract : Our objective is to compute the neighborhood degree-based topological indices via NM-polynomial for starphene. In the neighborhood degree-based topological indices, we compute the third version of the Zagreb index; neighborhood second Zagreb index; neighborhood forgotten topological index; neighborhood second modified Zagreb index; neighborhood general Randic index; neighborhood harmonic index; neighborhood inverse sum index; first, second, third, fourth, and fifth NDe indices; fourth atom bond connective index; fifth geometric arithmetic index; fifth arithmetic-geometric index; fifth hyper-first and second Zagreb index; general first neighborhood index; and Sanskruti index. These neighborhood topological indices are computed both direct and via the NM-polynomial approach.